Aerial survey techniques - Eltringham, S K (Wildfowl, 1959)
The object of the aerial surveys in North America is to provide data from which shooting regulations may be drawn up, and as these regulations are made in advance, it is necessary to make a forecast of what the duck crop is likely to be. The success of a breeding season depends on many factors, not the least of which is the amount of water available. A wet spring means full sloughs in the summer for the young ducklings and is a harbinger of a good shooting season. Thus, a forecast of next winter's duck population must take into account the amount of water available and the number of breeding pairs in the spring as well as the number and average size of the broods in the summer. From this information an index of the duck population is derived. In order to collect these data, a breeding population survey is flown in May and a production survey in July.